Clinical Assessment and Lesion-Specific Management of Orbital Vascular Malformations - Rootman, Daniel B.; Diniz, Stefania B.; Cohen, Liza M. (Journal of Neurological Surgery Part B: Skull Base, 2021)
The systematic classification of vascular disease as proposed and refined by the International Society for the Study of Vascular Anomalies (ISSVA) divides vascular pathology first into tumors and malformations. Malformations are described as simple and complex, where simple malformations contain a single vascular system and complex malformations comprised of multiple vascular systems. Arteriovenous malformations are considered in terms of inflow characteristics which are primarily responsible for the key management challenges. Management utilizing endovascular embolization and/or surgical resection is often employed; however, recurrence can occur, particularly in diffuse cases. There may be an increasing role for systemic antiangiogenic therapy in such cases. Lymphaticovenous malformations are divided into the principle components on the lymphatic and venous sides for clarity of discussion. Lymphatic malformations are described morphologically as macrocystic and microcystic, and physiologically in terms of the processes responsible for growth. In both cases, surgical options are challenging and local therapeutics intended to close large luminal spaces in the case of macrocystic and to slow biological signaling for growth in microcystic. Venous malformations are described physiologically in terms of flow and distensibility, as volume plays a critical role in the limited space of the orbital cavity. Combined embolic-surgical approaches can be effective for management. More complicated, combined lesions can be managed by dividing the lesion into principal components and treating each appropriately.
Keywords: orbital neoplasms; arteriovenous malformations; venous malformations; lymphaticovenous malformation; lymphatic malformation; sclerotherapy; interventional neuroradiology; intravascular embolization